IN MEMORIAM: PROFESSOR EMERITUS IBRAHIM AGANOVI´C (1934–2024) - Kulenović, Mustafa (Sarajevo Journal of Mathematics, 2025)
We are deeply saddened to announce the passing of Professor Emeritus Ibrahim Aganovi´c, who died on November 4, 2024, in Zagreb at the age of 90. Born on July 10, 1934, in Banja Luka, Professor Aganovi´c dedicated his entire academic career to the University of Zagreb, Croatia, where he made lasting contributions to mathematics and academic life.